COMPARISON OF CORETAX WITH DIGITAL TAX SYSTEMS IN ASEAN COUNTRIES: POLICY AND IMPLEMENTATION STUDY - Rossy Ananda (Journal of Strategic Behaviour Accounting, 2025)
This study presents a comparative analysis of Coretax, Indonesia’s centralized digital taxation system, against other digital tax systems implemented in ASEAN countries. As tax authorities across the region increasingly embrace digital transformation, disparities in policy design, technological readiness, and implementation efficiency have become more evident. Coretax demonstrates notable strengths in improving tax compliance, transparency, and administrative efficiency through features such as real-time data access, automated taxpayer profiling, and centralized audits. However, its effectiveness is challenged by infrastructural limitations, fragmented legal frameworks, and varying levels of digital literacy. By analyzing case studies from Singapore, Malaysia, Thailand, and the Philippines, this study highlights both common challenges and best practices in digital tax governance. Singapore and Malaysia are found to lead in system maturity and user experience due to their integrated platforms and strong institutional support. The research emphasizes the importance of aligning digital tax reforms with broader policy initiatives, regional integration strategies, and cybersecurity frameworks. Using a qualitative literature-based methodology, the study contributes to the academic discourse on fiscal digitalization by identifying key factors for successful implementation and recommending a path toward harmonized ASEAN digital tax policies. The findings offer practical insights for policymakers seeking to modernize tax systems while fostering inclusive economic development across the region.